Archives and documents for the study of political violence during the years of Popular Unity in Chile (1970-1973) - Morales Aguilera, Francisco Javier (Revista General de Información y Documentación, 2020)
Unlike other periods and historical events in Chile - which create a more systematic work of interpretation, revision and compilation of documentary sources - the problem of political violence during the years of the Popular Unity accuses unequal and insufficient development. As a way to fill this gap, this article proposes to reexamine a series of documentary archives that to date have been scarcely worked and that can provide new data and perspectives for study. Most of these documents focus on an individual dimension of the political violence of those years, particularly regarding the social actors that materialized or suffered it. From these documents, a significant part of some of the most critical problems through which the Chilean route through socialism can be reconstructed. The presentation of the archives and documents reviewed is preceded by a contextualization and bibliographic discussion that provides a more pertinent analysis framework to understand the contribution and usefulness of these resources.